PRECISION: A Reconfigurable SIMD/MIMD Coprocessor for Computer Vision Systems-on-Chip - Nieto, Alejandro; Vilarino, David L.; Brea, Victor M. (IEEE transactions on computers, 2016)
Computer vision applications have a large disparity in operations, data representation and memory access patterns from the early vision stages to the final classification and recognition stages. A hardware system for computer vision has to provide high flexibility without compromising performance, exploiting massively spatial-parallel operations but also keeping a high throughput on data-dependent and complex program flows. Furthermore, the architecture must be modular, scalable and easy to adapt to the needs of different applications. Keeping this in mind, a hybrid SIMD/MIMD architecture for embedded computer vision is proposed. It consists of a coprocessor designed to provide fast and flexible computation of demanding image processing tasks of vision applications. A 32-bit 128-unit device was prototyped on a Virtex-6 FPGA which delivers a peak performance of 19.6 GOP/s and 7.2 W of power dissipation.